2021
DOI: 10.1002/anie.202109714
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships in Nonenzymatic Template‐Directed RNA Synthesis

Abstract: The template-directed synthesis of RNAp layed an important role in the transition from prebiotic chemistry to the beginnings of RNAb ased life,b ut the mechanism of RNA copying chemistry is incompletely understood. We measured the kinetics of template copying with as et of primers with modified 3'-nucleotides and determined the crystal structures of these modified nucleotides in the context of ap rimer/ template/substrate-analog complex. pH-rate profiles and solvent isotope effects show that deprotonation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Hence the primer is extended one nucleotide at a time even though the intermediate is a dinucleotide. Previous studies have shown that the primer 3′-hydroxyl is deprotonated before the transition state 3 , consistent with an essential role for the catalytic Mg 2+ ion in lowering the p Ka of the 3′-hydroxyl by inner-sphere coordination with 3′O − .…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Hence the primer is extended one nucleotide at a time even though the intermediate is a dinucleotide. Previous studies have shown that the primer 3′-hydroxyl is deprotonated before the transition state 3 , consistent with an essential role for the catalytic Mg 2+ ion in lowering the p Ka of the 3′-hydroxyl by inner-sphere coordination with 3′O − .…”
Section: Introductionsupporting
confidence: 63%
“…In the catalytically favorable Mg 2+ coordination cases, this trend is reversed when Mg 2+ is bound to the Sp oxygen and the highest puckering amplitudes correlate with the shortest O3′-P distance in the major groove-facing 3′Osystem (Figure S15A). Since modified sugars can significantly impact the rate of the primer extension reaction, future computational studies incorporating sugars such as ANA, DNA, and LNA in the primer/template/bridged dinucleotide complex may reveal the contribution, if any, of increasing sugar pucker amplitude and related structural factors to the rate of the primer extension reaction 3,[47][48][49] . Because transient intermediate conformations cannot be sampled efficiently through conventional MD, alternative biased simulation strategies may provide further insights into the primer extension reaction.…”
Section: Discussionmentioning
confidence: 99%
“…[26,28] The difference in reactivity was observed for extension off a DNA primer occurring at only 5.3 h À 1 compared to 60 h À 1 for an RNA primer. [34] The difference in reaction rates was also observed for RNA or DNA nucleotides, with incorporation of a 2-aminoimidazole bridged G*G dimer proceeding at 44 h À 1 with an RNA G*G dimer compared to only 24 h À 1 with a DNA G*G dimer. [33] The effect is also observed when DNA is used as a template, with slower primer extension rates for DNA observed than for RNA, for the same primer and nucleotide system.…”
Section: Reactivity Difference Of Dna and Rnamentioning
confidence: 91%
“…[33] This variation is despite the nucleophilic attack of the primer 3'-OH being the rate limiting step for all activating agents. [34] The higher incorporation rate observed with the C*G dimers is a result of higher template occupancy from a higher k on rate and a lower k off rate. The greater k on versus k off results in more microstates of the 'bound complex' existing and therefore more opportunities for extension to occur.…”
Section: Nucleotide Incorporation Correlates With Template Occupancymentioning
confidence: 94%
“…Furthermore, the electronegativity of the 2′-substituent increasing reactivity 22 is a factor in the higher incorporation of the monomer with an RNA primer compared to a DNA primer. However, this does not explain the increase in the incorporation of a DNA nucleotide with a DNA primer of 19% (system 1 ) to 41% (system 5 ), when moving from a DNA to an RNA template, as there is no chemical difference in the 2′-substituents on the primer and nucleotide.…”
mentioning
confidence: 99%